Conceptual study of prospective audio reminder as cognitive support for medication compliance of elderly adults - Tan, Hee Kiah. (2008)
The advancements in microelectronic technology are making personal prospective audio reminding device a viable solution to improve medication adherence. This dissertation studies the effectiveness and explore the human factors issues relating to the use of a prospective audio reminder system to help elderly adults to be more compliance in taking their medication.